Analysis of the Effect of DNA Purification on Detection of Human Papillomavirus in Oral Rinse Samples by PCR - D'Souza, Gypsyamber; Sugar, Elizabeth; Ruby, William; Gravitt, Patti; Gillison, Maura (Journal of Clinical Microbiology, 2005)
Human papillomavirus (HPV) has recently been associated with oral cancers. To prepare for a study of the natural history of oral HPV infection, the effect of the DNA purification method on HPV genomic DNA detection in Scope mouthwash oral rinse samples and the reproducibility of HPV detection in rinse samples collected 7 days apart were investigated. The study was conducted with a population at high risk for oral HPV infection: human immunodeficiency virus-infected men with CD4-cell counts <200. Five DNA purification methods were compared among equal aliquots of oral rinse samples collected from a subset of individuals. The purification methods included (i) proteinase K digestion (PKD) and heat inactivation; (ii) PKD and ethanol precipitation (EP); (iii) PKD, phenol-chloroform extraction, and EP; (iv) use of the Puregene DNA purification kit; and (v) use of the QIAamp DNA Blood Midi kit. HPV was detected by PCR amplification with PGMY09 and PGMY11 L1 primer pools and by use of a Roche linear array. Puregene-purified samples had higher human DNA yields and purities, and Puregene purification detected the greatest number of HPV-positive subjects and total HPV infections in comparison to the numbers detected by all other methods. The total number of HPV infections and HPV prevalence estimates were also higher for Puregene-processed oral rinse samples when a fixed volume (10 [micro]l) rather than a fixed cell number ([approximately]50,000 cells) was used for PCR amplification. A good concordance was observed for oral HPV infection status (agreement, 80%; kappa value, = 0.60) and type-specific infection (agreement, 98%; kappa value, 0.57) in matched oral rinse samples. The method of DNA purification significantly affects the detection of HPV genomic DNA from oral rinse samples and may result in exposure misclassification that could contribute to the inconsistent associations reported in the literature.